2‐mercaptobenzothiazole generates γ‐H2AX via CYP2E1‐dependent production of reactive oxygen species in urothelial cells. Issue 6 (13th March 2022) - Qi, Yonggang; Toyooka, Tatsushi; Horiguchi, Hyogo; Koda, Shigeki; Wang, Rui‐Sheng
Abstract: Ortho ( o )‐toluidine is a widely known carcinogenic substance associated with cancers of the human bladder. A study on British chemical factory workers exposed to 2‐mercaptobenzothiazole, phenyl‐β‐naphthylamine, aniline, and o‐ toluidine demonstrated the crucial roles of o‐ toluidine, 2‐mercaptobenzothiazole, and phenyl‐β‐naphthylamine in the development of bladder cancer. As genotoxic events are crucial steps in the initiation of cancer, in the present study, we aimed to examine the genotoxic potential of the four chemicals using phosphorylated histone H2AX (γ‐H2AX), which is a sensitive and reliable marker of DNA damage, in cultured human urothelial cells. Of the four chemicals, 2‐mercaptobenzothiazole was a particularly potent DNA‐damaging agent. Moreover, mechanistic studies revealed that γ‐H2AX generation by 2‐mercaptobenzothiazole was mainly associated with the generation of reactive oxygen species via cytochrome P450 2E1‐mediated metabolism. The findings of this study may provide information that is important for the assessment of risks associated with chemicals as well as the interpretation of epidemiological studies investigating occupational bladder cancer.